The pheromone response pathway activates transcription of Ty5 retrotransposons located within silent chromatin of Saccharomyces cerevisiae. - Ke, N (1997)
The Saccharomyces retrotransposon Ty5 integrates preferentially into transcriptionally inactive regions (silent chromatin) at the HM loci and telomeres. We found that silent chromatin represses basal Ty5 transcription, indicating that these elements are encompassed by silent chromatin in their native genomic context. Because transcription is a requirement for transposition, integration into silent chromatin would appear to prevent subsequent rounds of replication. Using plasmid-borne Ty5-lacZ constructs, we found that Ty5 expression is haploid specific and is repressed 10-fold in diploid strains. Ty5 transcription is also regulated by the pheromone response pathway and is induced approximately 20-fold upon pheromone treatment. Deletion analysis of the Ty5 LTR promoter revealed that a 33 bp region with three perfect matches to the pheromone response element is responsible for both mating pheromone and cell-type regulation. Transcriptional repression of Ty5 by silent chromatin can be reversed by pheromone treatment, which leads to transcription and transposition. Ty5 replication, therefore, is normally repressed by silent chromatin and appears to be induced during mating. This is the first example of transcriptional activation of a gene that naturally resides within silent chromatin.